Point pacific express Legazpi travel hostel and railway terminal - Surtida, Francis Edgar O. (Quezon City College of Architecture, University of the Philippines Diliman, 2014)
Abstract
The past century witnessed the country’s rail operations change in management and gone through various rebranding. However, it is still faced with the same problems, resulting to its decline. Few changes on its physical structure were implemented.
Hence, this study seeks to propose an architectural solution, emphasizing on the complementary nature of the rail operations and tourism in backpacking trend through a facility design that houses both a travel hostel and a railway system in Legaspi City.
Using Central Location, Population, Market, and Existing Structures as criteria, a site was chosen form Bicol, which by popular culture has been already associated with the rail industry from the famous Bicol Express Line and Tourism.
With the aim of integrating the rail and hostel component into one structure, time sharing was employed to have the components segregated in terms of space, schedules of operations and peak occupancies in order to prevent overlapping lines of movements and overcrowding within the structure. The Design concept on the other hand focused on social spaces and mobility.
Through the galleries, hawkers market and social spaces, the culture is viewed as a dynamic element that is transforming and changing through time. This complements the nature of transport terminal which deals with floes movements or mobility. The integrated facility therefore embodies the image of the place by means of culture through the social spaces that were incorporated; and by physical manifestation as a medium for perceiving an impression of the place
Thesis (Bachelor of Science in Architecture)--University of the Philippines Diliman
Keywords: Railroad stations; Terminals (Transportation); Hostels